1993
DOI: 10.1002/ana.410340617
|View full text |Cite
|
Sign up to set email alerts
|

Parvalbumin‐immunoreactive cortical neurons in Creutzfeldt‐Jakob disease

Abstract: Massive abnormalities of parvalbumin-immunoreactive cortical neurons were observed in the cerebral biopsy samples of 3 patients with Creutzfeldt-Jakob disease. Immunoreactive cells had reduced and short, often fragmented, dendrites, and large numbers of dendritic varicosities were observed. Since parvalbumin-immunoreactive neurons are the most important inhibitory cells in the cerebral cortex, the damage to these neurons may account, in part, for the impaired cortical function, and may play a role in the appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
2
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 12 publications
6
25
2
1
Order By: Relevance
“…Pathological studies on the cortical interneurons have shown that there was relative sparing of PV and neuropeptide Y (NPY) expressing interneurons in the superior frontal cortex of HD cases (Cudkowicz and Kowall 1990) and Macdonald and Halliday (2002) showed no significant change in the interneuron populations defined by CB, CR, and PV in motor cortical regions in five HD cases examined in their study. In contrast, Ferrer et al (1994) observed a significant decrease in PV expressing interneurons in the frontal cortex, but significant difference was not observed in the occipital and temporal lobes. These results suggest that there is a heterogeneous topographical pattern of GABAergic interneuron loss in the different functional regions of the cortex in HD.…”
Section: Cerebral Cortexcontrasting
confidence: 64%
“…Pathological studies on the cortical interneurons have shown that there was relative sparing of PV and neuropeptide Y (NPY) expressing interneurons in the superior frontal cortex of HD cases (Cudkowicz and Kowall 1990) and Macdonald and Halliday (2002) showed no significant change in the interneuron populations defined by CB, CR, and PV in motor cortical regions in five HD cases examined in their study. In contrast, Ferrer et al (1994) observed a significant decrease in PV expressing interneurons in the frontal cortex, but significant difference was not observed in the occipital and temporal lobes. These results suggest that there is a heterogeneous topographical pattern of GABAergic interneuron loss in the different functional regions of the cortex in HD.…”
Section: Cerebral Cortexcontrasting
confidence: 64%
“…However, more experimental work is needed to test whether their synaptic input and plasticity matches that of new neurons in NBH mice, and whether they possess other intrinsic properties specific to young neurons such as the presence of T-type Ca 2+ channels which can boost fast Na + action potentials. The enhanced excitability of older neurons in prion mice may lead to aberrant activity, such as the EEG patterns observed in variant CJD cases (Ferrer et al , 1993; Lapergue et al , 2010) or experimental mice (Bassant et al , 1984; Jefferys et al , 1994) interfering with memory mechanisms (Jung and McNaughton, 1993; Skaggs et al , 1996), such as the impairments described in this model of prion disease (Cunningham et al , 2003). …”
Section: Discussionmentioning
confidence: 99%
“…Por ejemplo, la enfermedad de Creutzfelt-Jakob (encefalopatía espongiforme, también llamada de las "vacas locas") produce pérdida generalizada de PV en casi todo el encéfalo (33,34). Además, la inflamación de los nervios periféricos produjo un deterioro de la inmunotinción de este marcador en el asta dorsal en la médula de ratas (35).…”
Section: Efecto De La Infección Viral Sobre La Expresión De Cb Y Pvunclassified